2021
DOI: 10.4081/ejh.2021.3185
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 expression with QR1 and E1L3N antibodies according to histological ovarian cancer subtype: A series of 232 cases

Abstract: Therapeutic strategies for epithelial ovarian cancers are evolving with the advent of immunotherapy, such as PD-L1 inhibitors, with encouraging results. However, little data are available on PDL-1 expression in ovarian cancers. Thus, we set out to determine the PD-L1 expression according to histological subtype. We evaluated the expression of two PD-L1 clones – QR1 and E1L3N – with two scores, one based on the percentage of labeled tumor cells (tumor proportion score, TPS) and the other on labeled immune cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…Accumulating evidence suggests that, in OC, PD‐L1 is mostly expressed in tumor‐associated macrophages (TAMs), while IHC labeling of tumor cells is relatively uncommon 27,52 . Our study agrees with Eymerit‐Morin et al, who reported that PD‐L1 tumor cell labeling in OC is an uncommon event and a TPS score > 1%, using the E1L3N antibody, was found in just 14% of their cases 35 . Webb et al also reported PD‐L1 tumor cell positivity in just 13.2% of the tested OC cases, while TAMs were labeled in most of their cases 52 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Accumulating evidence suggests that, in OC, PD‐L1 is mostly expressed in tumor‐associated macrophages (TAMs), while IHC labeling of tumor cells is relatively uncommon 27,52 . Our study agrees with Eymerit‐Morin et al, who reported that PD‐L1 tumor cell labeling in OC is an uncommon event and a TPS score > 1%, using the E1L3N antibody, was found in just 14% of their cases 35 . Webb et al also reported PD‐L1 tumor cell positivity in just 13.2% of the tested OC cases, while TAMs were labeled in most of their cases 52 .…”
Section: Discussionsupporting
confidence: 91%
“…27,52 Our study agrees with Eymerit-Morin et al, who reported that PD-L1 tumor cell labeling in OC is an uncommon event and a TPS score > 1%, using the E1L3N antibody, was found in just 14% of their cases. 35 Webb et al also reported PD-L1 tumor cell positivity in just 13.2% of the tested OC cases, while TAMs were labeled in most of their cases. 52 Three recent studies correlated PD-L1 immunohistochemical status between primary OC lesions and their paired metastases (Table 3); all of them utilized tissue rather than cytologic samples.…”
Section: Pd-l1 (M) 22c3mentioning
confidence: 88%
See 2 more Smart Citations
“…To date, there are no recommendations for evaluating immunohistochemical PD-L1 expression for targeted therapy in the first-line treatment of OCs (INCa). 30 But some studies confirm the rationale for using immunotherapy in ovarian cancer patients. PD-1/PD-L1 expression in OC is the main rationale for using immunotherapy in this malignancy.…”
Section: Pd-1/pd-l1/pd-l2 As Therapeutic Targets and Their Significan...mentioning
confidence: 99%